Assessing the Relationship Between a Peer-Mentoring Program and Case Outcomes in Dependency Court. Issue 2 (14th March 2016) - Bohannan, Theresa; Gonzalez, Carlene; Summers, Alicia
Abstract : Building successful family-centered programs to support families whose children have been removed can be especially challenging to child welfare agencies. Peer-mentoring programs match families new to the dependency system with a mentor who has successfully reunified with their children. The current study examines the relationship between a peer-mentoring program, Parent for Parent ( P4P ), engagement levels of parents, and case outcomes for these families. Findings revealed that participants in the peer-mentoring program experienced increased engagement levels and improved outcomes for their cases. Specifically, mothers and fathers who participated in P4P increased their compliance with case plans and visitation, as well as increased presence at court hearings. Reunification rates increased for all families who participated in the peer-mentoring program, compared to those who did not. Few associations were found between racial and ethnic groups and program participation. The implications of these findings and suggestions for future research are discussed.